The Sri Lankan Malays and their language = Orang Melayu Sri Lanka dan bahasanya - Saldin, B. D. K. (Kurunegala Nihon Printers, 2001)
Comparison of the Malay language spoken by the Malays in Sri Lanka with those in Malaysia and Indonesia.
English, Malay, and Indonesian.
Keywords: Malay language -- Sri Lanka; Malays (Asian people) -- Sri Lanka